Barriers to Physical Activity in Low Back Pain Patients following Rehabilitation: A Secondary Analysis of a Randomized Controlled Trial. (25th October 2017) - Schaller, Andrea; Exner, Anne-Kathrin; Schroeer, Sarah; Kleineke, Vera; Sauzet, Odile
Abstract : Background. Promoting health-enhancing physical activity following rehabilitation is a well-known challenge. This study analysed the barriers to leisure time activity among low back pain patients. Methods. A subset of 192 low back pain patients who participated in a randomized controlled trial promoting physical activity was analysed. Physical activity, barriers, and sociodemographic and indication-related variables were assessed by a questionnaire. Differences in barriers between active and inactive participants were tested by Pearson's chi squared test. A logistic regression model was fitted to identify influencing factors on physical activity at six months following rehabilitation. Results. Inactive and active participants differed significantly in nine of the 19 barriers assessed. The adjusted regression model showed associations of level of education (OR = 5.366 [1.563; 18.425]; p value = 0.008) and fear of pain (OR = 0.612 [0.421; 0.889]; p value = 0.010) with physical activity. The barriers included in the model failed to show any statistically significant association after adjustment for sociodemographic factors. Conclusions. Low back pain patients especially with a low level of education and fear of pain seem to need tailored support in overcoming barriers to physical activity. This study is registered at German Clinical Trials Register (DRKS00004878 ).